2007
DOI: 10.1007/s12094-007-0110-8
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic metastases from ductal and lobular carcinomas of the breast

Abstract: The pancreas is an uncommon target for metastases from other primary tumours. We discuss clinical, diagnostic and therapeutic aspects of pancreatic metastases through presentation of two surgically treated cases of metastases originating from breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…After extensive online research, we identified 23 studies, 17 case reports and 6 case series, totaling 28 reported cases of pancreatic metastases from breast cancer. Table 2 2 , 3 , 6 , 7 , 8 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 summarizes the main articles found and their reported outcomes. Figure 3 presents a flow diagram of the articles selected.…”
Section: Discussionmentioning
confidence: 99%
“…After extensive online research, we identified 23 studies, 17 case reports and 6 case series, totaling 28 reported cases of pancreatic metastases from breast cancer. Table 2 2 , 3 , 6 , 7 , 8 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 summarizes the main articles found and their reported outcomes. Figure 3 presents a flow diagram of the articles selected.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, there have been only few cases of pancreatic-metastasis from carcinoma breast reported in the literature so far. [23456]…”
mentioning
confidence: 99%
“…[6] Although surgery is considered, a first-choice treatment in selected patients with pancreatic metastases but it is associated with significant morbidity. [11] Moreover, the option for resection should mainly be reserved for the case of metastatic processes limited to the pancreas and amenable to surgical resection.…”
mentioning
confidence: 99%